Redefining those subtle borders: transhumanism, frontiers, retroprogression and hermeneutics at the crossroads of teaching - Francisco Carrera, Francisco José (Frontiers in Education, 2024)
The world of education is undergoing many changes, this implies that worthwhile views coming from the past can be totally lost in the acceleration we are experiencing. Transhumanism, as a tendency, seems to imply a moving forward at a increasing speed. Therefore, it would be interesting to reflect on Transhumanism but in relation to Retro-progression and Phronesis, to be able to understand how limits work in the realm of education. Interpretation, then, is one of the basic tools for the educators in this very complex environment, their role as meta-interpreters can be founded in a return to hermeneutics as an art and a science. In so doing, past and future are reconciled in the present and the transhumanist principles do keep in mind the human part of the term. We conclude that Education is always an act of human understanding that implies the full attention and presence of the educator who is therefore able to offer meaningful actions by understanding properly the hereand-now and uniqueness of every teaching situation.